Technical-tactical strategies in grassroots football (Quaestiones Disputatae: temas en debate, 2025)
This reflection article analyzes the strategies, techniques - tactics used in the development of grassroots football in training schools, it has become an important instrument of socialization and use of free time that through the game seeks to be able to enjoy the more playful face of sport; without forgetting that in order to do it in a healthy way it is necessary to acquire training from an early age, thus they will be able to form habits that train the athlete in an integral way.Through this information, the activities carried out in sports or school recreation spaces are made known, with children and young soccer players applying various teaching and learning methods in tactical, technical and motivational aspects for the integral development of the athlete.
Keywords: Free time, base soccer, school sports, soccer coaches.